PEMANFAATAN EKSTRAK TANAMAN SIRIH WATI (Piper methysticum G. Forst.) SEBAGAI INSEKTISIDA NABATI DALAM MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera litura F.): PEMANFAATAN EKSTRAK TANAMAN SIRIH WATI (Piper methysticum G. Forst.) SEBAGAI INSEKTISIDA NABATI DALAM MENGENDALIKAN HAMA ULAT GRAYAK (Spodoptera litura F.) - Inrianti; Sepling Paling; Tebina Wenda (Universitas PGRI Adi Buana Surabaya, 2023)
The aim of the study was to determine the effect of various concentrations of betel leaf extract Wati (Piper methysticum G. Forst.) on the mortality rate of armyworm (Spodoptera litura F.) and to see which extract concentration is more effective in controlling armyworm pest (Spodoptera litura F.) in sweet potato (Hypere). This research was conducted from June to August 2019 at the Petra Baliem Wamena College of Agricultural Sciences Laboratory using a non-factorial Completely Randomized Design (CRD) with 6 treatments and 4 replications. Tests using betel leaf extract (Yulliaoken) with a concentration of 40%, 50%, 60%, 70%, 80%, 90%. Measurements were made on the mortality rate of armyworms in the form of a percentage (%). This research was carried out through 2 stages, namely: the preliminary test stage and the follow-up test stage. The results showed that Wati betel leaf extract (Piper methysticum G. Forst.) can increase the mortality of armyworm pests (Spodoptera litura F.) by administering the extract through immersion so that through feed, Wati betel leaf extract has the potential to be a stomach poison. The most effective concentration of betel leaf extract in increasing the mortality of second instar armyworm caterpillars was at concentrations of 80% and 90% within 5 hours. Thus, Wati betel leaf extract can be used as an effective vegetable insecticide in increasing the mortality of armyworm pests.